Large national series of patients with Xq28 duplication involving MECP2: Delineation of brain MRI abnormalities in 30 affected patients. Issue 1 (30th September 2015) - El Chehadeh, Salima; Faivre, Laurence; Mosca‐Boidron, Anne‐Laure; Malan, Valérie; Amiel, Jeanne; Nizon, Mathilde; Touraine, Renaud; Prieur, Fabienne; Pasquier, Laurent; Callier, Patrick; Lefebvre, Mathilde; Marle, Nathalie; et al.
Abstract : Xq28 duplications encompassing MECP2 have been described in male patients with a severe neurodevelopmental disorder associated with hypotonia and spasticity, severe learning disability, stereotyped movements, and recurrent pulmonary infections. We report on standardized brain magnetic resonance imaging (MRI) data of 30 affected patients carrying an Xq28 duplication involving MECP2 of various sizes (228 kb to 11.7 Mb). The aim of this study was to seek recurrent malformations and attempt to determine whether variations in imaging features could be explained by differences in the size of the duplications. We showed that 93% of patients had brain MRI abnormalities such as corpus callosum abnormalities (n = 20), reduced volume of the white matter (WM) (n = 12), ventricular dilatation (n = 9), abnormal increased hyperintensities on T2‐weighted images involving posterior periventricular WM (n = 6), and vermis hypoplasia (n = 5). The occipitofrontal circumference varied considerably between >+2SD in five patients and <−2SD in four patients. Among the nine patients with dilatation of the lateral ventricles, six had a duplication involving L1CAM . The only patient harboring bilateral posterior subependymal nodular heterotopia also carried an FLNA gene duplication. We could not demonstrate a correlation between periventricular WM hyperintensities/delayed myelination and duplication of the IKBKG gene. We thus conclude that patients with an Xq28 duplication involving MECP2 share some similar but non‐specific brain abnormalities. These imaging features, therefore, could not constitute a diagnostic clue. The genotype–phenotype correlation failed to demonstrate a relationship between the presence of nodular heterotopia, ventricular dilatation, WM abnormalities, and the presence of FLNA, L1CAM, or IKBKG, respectively, in the duplicated segment. © 2015 Wiley Periodicals, Inc.